The influence of variable feed rate on bushing and surface roughness in friction drilling - Ozler, Latif (Springer Heidelberg, 2019)
In this study AISI 1010 square-section material was drilled on CNC milling machine using friction drilling processes in two different patterns, namely constant feed rate and variable feed rate. In both drilling processes the tool-workpiece contact region temperatures, drilling forces, surface roughness and bushing profiles were examined. The drilling processes with constant feed rate used 50, 100 and 150mm/min feed rate values. In drilling processes with variable feed rate, the feed rate values were increased constantly from 50mm/min to 100, 150 and 200mm/min during drilling. According to experiment results, in drilling with variable feed rate, tool-workpiece contact area temperature and bushing height increased. It has been witnessed that in the two different low feed rate drilling processes, no significant difference occurred in the petal structure of bushing. In 50-100mm/min variable feed rate which provided the best bushing and petal structure, drilling time was reduced some 50% compared to drilling with 50mm/min constant feed rate.
Keywords: Friction drilling; Bushing geometry; Surface roughness; Drilling temperature; Thrust forces